Factors Affecting The Trust Of Fintech Users In The State Saving Bank Of The Sharia Branch Office Medan - Asrika, Winri; Rahmayati, Rahmayati (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2022)
The purpose of this study was to determine whether or not there is an influence of convenience, security, service on the trust of fintech (financial technology) users, this type of research is associative. The location of this research was conducted at the State Savings Bank (Persero) Medan Syariah Branch Office which is located at Jalan Haji Juanda No.48, Medan Maimun, Suka Damai, Kec. Medan Polonia, Medan City, North Sumatra, the population is all customers at PT. State Savings Bank (Persero) Medan Syariah Branch Office taken as many as 261 customers, the sample in this study was 72 people, the analytical technique used in this study was multiple linear regression analysis, In this study the Ease of Variable affects the use of Fintech at BTN Syariah because the value t count t table (2.6951.994) and the significance level is lower than 0.05, namely 0.009 (0.009 0.05). In this study, the security variable affects the use of Fintech at BTN Syariah because the value of t count t table (3.7721.994) and a significant level lower than 0.05, namely 0.001 (0.001 0.05). BTN Syariah due to the value of t arithmetic t table (7.6951.994) and a significant level lower than 0.05, namely 0.000 (0.000 0.05), There is an effect of service on fintech users at the State Savings Bank (Persero) Medan Syariah Branch Office, , Bank Tabungan Negara Syariah continues to improve services using fintech. In this study, convenience, security, and services together affect fintech users at the State Savings Bank (Persero) Medan Syariah Branch Office as seen from f count / f table (51.110 2.74) and the significantlevel which is 0.000 is less than 0.05 (0.000 0.05).